On the island of Zanzibar people in the community are frequently colonized with the same MDR Enterobacterales found in poultry and retailed chicken meat. (20th June 2020) - Büdel, Thomas; Kuenzli, Esther; Campos-Madueno, Edgar I; Mohammed, Ali Haji; Hassan, Nadir Khatib; Zinsstag, Jakob; Hatz, Christoph; Endimiani, Andrea
Abstract: Objectives: Intestinal colonization with extended-spectrum cephalosporin-resistant (ESC-R) and colistin-resistant (CST-R) Enterobacterales (Ent) can be driven by contact with colonized animals and/or contamination of the food chain. We studied the ESC-R-Ent and COL-R-Ent colonizing poultry as well as contaminating chicken meat in Zanzibar (Tanzania). Results were compared with recently published data obtained from rectal swabs of people in the community. Methods: During June and July 2018, we collected poultry faecal material ( n = 62) and retail chicken meat ( n = 37) samples. ESC-R and CST-R strains were isolated implementing selective approaches and characterized with different molecular methods, including WGS coupled with core-genome analyses. Results: The prevalence of ESC-R-Ent and CST-R-Ent, respectively, were: 88.7% and 48.4% in poultry; and 43.2% and 18.9% in chicken meat. Overall, the following strains and main resistance mechanisms were found in the two settings: 69 ESC-R Escherichia coli (CTX-M-15 subgroup, 75%), 34 ESC-R Klebsiella pneumoniae (CTX-M-9 group, 54.5%), 24 non-ESC-R but CST-R E. coli ( mcr-1, 95.8%) and 17 non-ESC-R but CST-R K. pneumoniae (D150G substitution in PhoQ). Several clones (differing by only 0–13 single nucleotide variants) were concomitantly and frequently found in human and non-human settings: mcr-1 -carrying E. coli ST46; CTX-M-15-producing E. coli ST361; CTX-M-14-producing K. pneumoniae ST17; and CTX-M-15-producing K. pneumoniae ST1741. Conclusions: This is one of the few studies that have assessed the occurrence of identical MDR Enterobacterales in human and non-human settings. The frequent human gut colonization observed in the community might be favoured by the spread of ESC-R-Ent and CST-R-Ent in poultry and chicken meat. Further studies with a One Health approach should be carried out to better investigate this phenomenon.